Working Spanish for homeowners - Stein, Gail (Wiley, 2008)
Practical, on-the-job help for homeowners who work with Spanish-speaking domestic employees. This compact, phrase-packed resource provides all the vocabulary that homeowners need to communicate effectively with Spanish-speaking house-keepers, cooks, nannies, gardeners, handymen, and other household workers. It's written expressly for homeowners, so users will find all of the phrases and vocabulary they need to tackle everything from grocery shopping to child care. Complete with pronunciations for all listings, this hands-on guide efficiently bridges the communication gap.